422 An open-label, multicenter, phase 1/2 clinical trial of RP1, an enhanced potency oncolytic HSV, combined with nivolumab: updated results from the skin cancer cohorts. (9th November 2020) - Middleton, Mark; Aroldi, Francesca; Sacco, Joseph; Milhem, Mohammed; Curti, Brendan; MBioeth, Ari VanderWalde; Baum, Scott; Samson, Adel; Pavlick, Anna; Chesney, Jason; Niu, Jiaxin; Rhodes, Terence; et al.
Abstract : Background: RP1 is an enhanced potency oncolytic HSV encoding a fusogenic protein (GALV-GP R-) and GM-CSF which has previously demonstrated tolerable safety and tumor regression alone and with nivolumab in patients with a number of tumor types. Updated data from the phase 1 expansion with nivolumab, melanoma phase 2 (enrollment complete) and non-melanoma skin cancer (NMSC; enrollment ongoing) cohorts will be presented (NCT03767348 ). Enrollment of a further 125 patient anti-PD1 refractory cutaneous melanoma cohort; and activation of a cohort of anti-PD1 refractory NSCLC is underway. Methods: Stage IIIb-IV melanoma patients for whom anti-PD-1 was indicated or who were refractory to prior anti-PD-1 alone or in combination with anti-CTLA-4, were enrolled. NMSC patients were anti-PD1 naïve. Patients received ≤8 doses of RP1 (≤10 mL/visit Q2W; first dose 10 6 PFU/mL then 10 7 PFU/mL) with nivolumab (240 mg IV Q2W for 4 months then 480 mg IV Q4W up to 2 years) from the second RP1 dose. Results: As of 24th June 2020, 36 melanoma and 16 NMSC patients had been enrolled with follow up of <1–17 months. Of the melanoma patients, 16 previously anti-PD1 treated cutaneous (8 also prior anti-CTLA-4), 8 anti-PD1 naïve cutaneous, 6 mucosal, and 6 uveal. Of the NMSC patients, 10 had squamous cell (CSCC), 3 had a basal cell, 1 had Merkel cell carcinomas, and 2 had angiosarcoma. Treatment emergent adverse events (TEAEs) remain consistent with phase 1, with RP1 side effects generally of Grade 1/2 constitutional-type symptoms, with no exacerbation of the side effects expected for nivolumab. At the data cut-off, 5 previously anti-PD1 treated (4 also anti-CTLA-4) cutaneous melanoma patients, 4 anti-PD1 naïve cutaneous melanoma patients, two mucosal melanoma patients (one anti-PD1 refractory) and one uveal melanoma patient (ipi/nivo refractory) have achieved response (WHO criteria for uveal). For NMSC, for the 13 patients with >8 weeks follow up, one of two angiosarcoma patients and seven of eight CSCC patients (5 CR) have achieved response (CSCC ORR 87.5%; CR rate 62.5%, including of uninjected visceral disease). Tumor biopsies in patients continue to routinely show immune activation, including robust recruitment of CD8+ T cells, reversal of T cell exclusion, and increased PD-L1 expression. Treatment remains ongoing, and current data will be presented. Conclusions: RP1 and nivolumab have continued to be well tolerated, with continued promising anti-tumor activity in patients with skin cancers, including those with anti-PD1 refractory and other difficult to treat melanomas, and in patients with CSCC.